Emergence of Aeromonas veronii strain co-harboring blaKPC–2, mcr-3.17, and tmexC3.2-tmexD3.3-toprJ1b cluster from hospital sewage in China - Zhu, Zhichen; Wu, Shuhua; Zhu, Jie; Wang, Tao; Wen, Yicheng; Yang, Chengcheng; Lv, Jinnan; Zhang, Haifang; Chen, Liang; Du, Hong (Frontiers in Microbiology, 2023)
The raise of multi-drug resistant bacteria involving carbapenem, colistin or tigecycline resistance causes threat to public health, which partly results from the transmission of corresponding mobile resistant genes, such as blaKPC and blaNDM for carbapenem, mcr for colistin, and tmexCD-toprJ gene cluster for tigecycline. Herein, we described the emergence of an Aeromonas veronii strain HD6454 co-harboring blaKPC-2, mcr-3.17, and tmexC3.2-tmexD3.3-toprJ1b gene cluster from hospital sewage. Whole genome sequencing (WGS) was used to determine the genome sequence of HD6454, and the detailed genomic analysis of genetic elements or regions carrying key antimicrobial resistance genes (ARGs) from HD6454 were performed. Cloning experiment was conducted to confirm the function of key ARGs in mediating antimicrobial resistance. Conjugation experiment was conducted to determine the mobility of the plasmid. The results showed that this strain belonged to a novel sequence type (ST) variant ST1016, and carried 18 important ARGs. Among them, the blaKPC-2 was carried by nonself-transmissible IncP-6 plasmid, while tmexC3.2-tmexD3.3-toprJ1b gene cluster and mcr-3.17 were carried by integrative and mobilizable element (IME) or IME-related region in chromosome. The mcr-3.17, mcr-3.6 and mcr-3-like3 genes were further inferred to originate from IMEs of Aeromonas species. Additionally, for the first time, the mcr-3.17 was confirmed to confer low-level resistance to colistin under inducible expression, while tmexC3.2-tmexD3.3-toprJ1b gene cluster was confirmed to confer low-level resistance to tigecycline. This is the first report of a strain co-harboring blaKPC-2, mcr-3.17, and tmexC3.2-tmexD3.3-toprJ1b gene cluster. Although the resistance and/or mobility of these ARGs are limited in this strain, the emergence of this multiple important ARGs-carrying strain deserves further attention.